Hubungan Pendidikan dan Wilayah Tempat Tinggal Dengan Pernikahan Dini Pada WUS di Provinsi Banten - Roslina Roslina (Jurnal Obstretika Scientia, 2021)
Marriage is a sacred process in human life. From various kinds of marriages, there is one phenomenon regarding marriage, namely early marriage. The purpose of this study was to determine the relationship between education and area of residence with early marriage in female sex workers in the province of Banten.Marriage is an activity that changes something that is forbidden to be halal with the conditions that a valid marriage has been fulfilled, but what has become a phenomenon in Indonesia, especially in the Banten region, is the high number of early marriages that occur. This is because there are some thoughts from the community that marrying their child immediately then he no longer needs to take care of the maintenance for the child, relinquishing his responsibilities as a parent if the child is a girl. National Riskesdas data in 2014, South Kalimantan Province was ranked 2nd after West Java in cases of early marriage at the youngest age between 10-14 years. Based on BKKBN data, the number of adolescent families in South Kalimantan is 2483 people with the number of early marriages reaching 18% of the total number of adolescents aged 14-16 years. It's a tough task for all of us to overcome this phenomenonThis research is a quantitative research, using descriptive research method with a cross-sectional approach (cross-sectional). The population is 1117 respondents and the entire population is sampled (saturated sample). The tool used in this research is a questionnaire. Data analysis using Chi-Square test. The results showed that the factors influencing early marriage from the results of the study showed that WUS who had early marriage had a greater proportion in the group that did not receive formal education (33.7%) compared to the group who received formal education (33.7%) compared to the group that received formal education. the group that received formal education (31%), P value (0.00) α which means that there is a relationship between education and early marriage. The OR value is 2.106 that respondents who do not receive formal education have a 2-fold risk for early marriage Keywords: education, early marriages, residence.